Digital addiction and its impact on the mental wellbeing of adolescents - Kaur, Gurmeet; Mehndroo , Meghna (Journal of Interdisciplinary Studies in Education, 2024)
Digital addiction has become an intriguing concern over the recent years because of the rapid explosion of gadgets and other online platforms attracting youth to spend most of their time online. Excessive use of digital platforms has been associated with many psychological issues. The results revealed significant correlations among digital addiction, depression and stress among both males and females. Males were more likely to be digitally addicted than females were. In contrast there were females on the depression scale. The study emphasizes the need to implement robust policies for schools and other educational institutes to make healthy practices for using digital media and to create alertness regarding the adverse effects of digital addiction over mental health.